Bentracimab demonstrates reversal of antiplatelet effects of ticagrelor: impact of hematocrit and generic versions of ticagrelor in vitro. (3rd October 2022) - Curry, B; Brown, R; Bhatt, D; Arnold, S; Lee, J; Jennings, L
Abstract:  : Recent clinical studies demonstrated bentracimab provides immediate and sustained reversal of ticagrelor's antiplatelet effects in patients undergoing surgical procedures or with bleeding. Ticagrelor reversal was assessed by VerifyNow PRUTest (VN) and other platelet function testing assays in Phase I-III studies. As decreases in hematocrit (hct) may impact the VN result, it remains to be demonstrated whether this assay can detect platelet function restoration by bentracimab in bleeding patients with low hct. Additionally, bentracimab utility against generic ticagrelors is unknown. The purpose of this study was to determine the impact of decreased hct and generic forms of ticagrelor on platelet function and subsequent reversal by bentracimab, as measured by light transmission aggregometry (LTA) and VN. The hct level in blood samples collected from healthy volunteers (n=10) was sequentially lowered to 32, 30, 25, 22.5, 20 or 15% by addition of autologous platelet-rich plasma to whole blood with matching platelet counts. Prepared samples were treated with nothing, vehicle, or ticagrelor (3.0 μg/mL) followed by treatment with bentracimab (1.2 mg/mL). In a separate study, blood collected from healthy volunteers (n=10) was treated with nothing, vehicle, ticagrelor or generic ticagrelors (3.0 and 5.6 μg/mL; mean and peak plasma levels in the Phase 1 trial) prior to addition of bentracimab (0, 0.6, 1.2, 1.8 and 2.4 mg/mL; below the reported minimum to peak plasma level) to demonstrate a dose response. Reversal was assessed by either ADP-mediated LTA or VN or both assays. Results show a decrease in hct to <30% significantly increased the PRU in untreated samples (p<0.05). Ticagrelor treatment significantly decreased the PRU in all hct groups (p<0.0001). When normalized to each donor's baseline PRU values, bentracimab reversed the ticagrelor effects within 10-min, restoring the PRU value to 54–73% for all hct groups. PRU values were further restored to 85–93% of baseline PRU after 1-hr treatment. The PRU inhibition for both 10-min and 1-hr treatments were not significantly different across the hct groups, except for the 10-min treatment in the 15% hct group vs. unadjusted hct group (p<0.05), suggesting equivalent reversal by bentracimab across the hct range. In the second study, treatment with generic ticagrelor demonstrated significant platelet inhibition and was comparable to standard ticagrelor. Bentracimab (>0.6 mg/mL) immediately restored platelet function after ticagrelor treatment to 80–100% of baseline using the VN test. LTA data demonstrated similar results to VN, but as expected, reversal was less robust with 5.6 μg/mL ticagrelor + 0.6 mg/mL bentracimab combination (mean 55% of baseline values). Collectively, these data suggest the VN test can effectively measure the antiplatelet effects of ticagrelor and subsequent reversal, even at low hct, and bentracimab is also capable of reversing the antiplatelet effects of generic forms of ticagrelor. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): PhaseBio Pharmaceuticals, Inc